(untitled) (Ameghiniana, 2013)
The following conclusions are based on analysis of data existing in the literature as well as on my own unpublished studies of the fauna (mainly foraminiferal) of the Southwestern Atlantic from the Miocene through the Recent. The Drake Passage did not exist in the Miocene, consequently neither did the Malvin Current exist. A connection between the Pacific and Atlantic Oceans was by means of the Austral Strait in the southernmost part of the Southamerican continent, where the Austral sedimentary basin is located. The Brazil Current formed a western part of the large anticyclonic gyre and penetrated farther to the south. The climate was warmer than now and boundaries between zoogeographical units, corresponding to Recent boundaries, were located at higher latitudes. The coastal outlines were different from Recent outlines, primarily in the southern part of the continent (Austral Strait) and in the Río de la Plata area, where a broad passage probably existed which ran meridionally across South America and connected the Caribbean sea with the South Atlantic Ocean. Very important geological events coincided approximately with the Miocene/Pliocene boundary, namely: rise of the main part of the Andes, closing of the Austral Strait and opening of the Drake Passage. The Circumpolar Antarctic Current and its branch, the Malvin Current, were established. The latter created a rather sharp temperature decrease in the Argentine shelf and displacement of the zoogeographical boundaries to the north. In the Pliocene, and more so in the Pleistocene, the climate was colder than now but the coastal outline was practically the same. Several transgressions and two glaciations occurred in the Pleistocene; these glaciations can be correlated with the European Early Würm and MainWünn. The fauna of benthic foraminifera of the shelf during the Miocene was strikingly similar to that of the Recent. This similarity signifies that evolution of benthic foraminifera is extremely slow not only at great depths but even in shalIow waters.